STRATEGI PENCEGAHAN NARKOBA BERBASIS MASYARAKAT DI KECAMATAN SIMPANG RIMBA,DESA SERDANG KABUPATEN BANGKA SELATAN - VIRNA DEWI (Fakultas Hukum Universitas IBA Palembang, 2020)
Abstract Narcotics and Drugs (Narcotics) or Narcotics, Psychotropics, and Additives (NAPZA) are substances that can increase the level of psychiatric or nutrition that can be adjusted to health and psychology. An important problem in this study is the threshold What is the Community Based Drug Prevention Strategy and the support of the Regional Government in the Prevention of Drug Use in Serdang Village, South Bangka Regency? The program for eliminating drug abusers has run according to existing normative standards. Every program if not carried out and the evaluation will not succeed, such as the formation of peer counselors, anti-drug youth cadres, and anti-drug integration curriculum. Based on the Regent's Decree, to maximize program implementation cross sectoral cooperation is needed. It is also in accordance with one of the HIAP strategies, namely cross-sectoral cooperation. The community has an important role in approving drugs. The public has begun to respond positively and take an active role in opposing drug abusers. The formation of peer counselors, anti-drug youth cadres, the role of parents, the role of BK teachers have started to run well.